Design and analysis of algorithms - Mohan, I. Chandra (New Delhi, India : PHI Learning Private Limited, 2012)
This book, on Design and Analysis of Algorithms, in its second edition, presents a detailed coverage of the time complexity of algorithms. In this edition, a number of chapters have been modified and updated with new materials. It discusses the various design factors that make one algorithm more efficient than others, and explains how to devise the new algorithms or modify the existing ones.
1, Fundamentals -- 2. Divide-and-Conquer Methods -- 3. The Greedy Method -- 4. Set Manipulation Algorithms -- 5. Dynamic Programming -- 6. Search and Traversal Techniques -- 7. Backtracking Methods -- 8. Branch-and-Bound Methods -- 9. Algebraic Simplification and Transformation -- 10. Lower Boundary Theory and NP-Hard and NP-Complete Problems -- References -- Index.
Includes index.
Keywords: COMPUTER ALGORITHMS